Utilization of HDPE (High Density Polyethylene) Plastic Waste as A Substitute for Some Cement in the Compressive Strength of Paving Blocks - Alaydrus, Syarifah Umi Qurani; Wicaksono, Kukuh Ary; Rabihati, Etty; Hafiyyan, Qalbi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2026)
Even in Indonesia, people are starting to take notice of the growing problem of plastic waste in the environment. West Kalimantan is one of many areas in Indonesia that still struggles with garbage management. Waste production will rise in tandem with the population. Hence, one possible solution to this insufficient waste problem is the production of paving blocks from plastic waste. Based on the findings, high-density polyethylene (HDPE) plastic material can replace some of the cement in paving block production. This study employs an experimental approach by fabricating paving blocks with plastic as a partial substitute for cement. A type of plastic known as High Density Polyethylene (HDPE) is utilized. As part of the curing process, two kinds of water PDAM water and peat groundwater are used. Paving blocks made with 0%, 2.5%, 5%, 7.5%, 10%, or 12.5% HDPE plastic as a partial cement substitute have a significant impact on the compressive strength of the finished product. At 14 days, the highest compressive strength value was achieved with a 2.5% plastic mixture curing in PDAM water at 21.163 MPa, followed by 20.472 MPa with peat soil water; at 28 days, the highest value was 19.403 MPa with 0% PDAM water, and at 19.32 MPa with 2.5% peat water. Paving blocks made with plastic as a partial cement substitute have an even greater absorption capacity after 14 and 28 days. The plastic paving block with a 2.5% peat variation absorbed 5.1% of the groundwater and the plastic mixture with no PDAM absorbed 4.6% of the water. It follows that high-density polyethylene (HDPE) plastic is not very good at absorbing water.